Preparation of Hydrophilic Hyper-Cross-Linked Polystyrene Nanospheres with Antibacterial for Improved Water Lubrication Performance - Wang, Yixin (Langmuir : the ACS journal of surfaces and colloids, 2024)
The present study utilizes styrene as a raw material to prepare hyper-cross-linked polystyrene nanospheres (HPSs) through the Friedel-Crafts reaction, establishing stable covalent bond structures within the polymer chains. The hydrophilic polystyrene nanospheres─TMASHPSs were successfully synthesized via sulfonation and ion exchange reactions, demonstrating exceptional properties in reducing friction and wear. Compared with pure water, the addition of 4.0 wt % TMA@SHPSs results in a 62.2% reduction in the friction coefficient, accompanied by a significant decrease to 1.17 × 105 μm3 in wear volume. The results demonstrate that TMA@SHPSs, as water-based lubrication additives, generate composite protective films (tribo-chemical protective films and physical protective films) during the friction process, which effectively prevents direct contact between the friction pairs and achieves remarkable antifriction and antiwear effects. The results of the antimicrobial activity test indicate that TMA@SHPSs demonstrate exceptional antibacterial efficacy due to the bacteriostatic effect induced by hydration and the bactericidal properties of quaternary ammonium cations